An Interplay Between Pericytes, Mesenchymal Stem Cells, and Immune Cells in the Process of Tissue Regeneration - Vladislav Volarevic; Carl Randall Harrell; Aleksandar Arsenijevic; Valentin Djonov (Analytical Cellular Pathology)
Immediately after injury, damaged cells elicit tissue regeneration, a healing process that enables optimal renewal and regrowth of injured tissues. Results obtained in a large number of experimental studies suggested that the cross talk between pericytes, mesenchymal stem cells (MSC), tissue-resident stem cells, and immune cells has a crucially important role in the regeneration of injured tissues. Pericytes, MSCs, and immune cells secrete bioactive factors that influence each other’s behavior and function. Immune cells produce inflammatory cytokines and chemokines that influence pericytes’ migration, proliferation, and transition to MSC. MSC releases immunoregulatory factors that induce the generation of immunosuppressive phenotype in inflammatory immune cells, alleviating detrimental immune responses in injured tissues. MSC also produces various growth factors that influence the differentiation of tissue-resident stem cells into specific cell lineages, enabling the successful regeneration of injured tissues. A better understanding of molecular mechanisms that regulate crosstalk between pericytes, MSC, and immune cells in injured tissues would enable the design of new therapeutic approaches in regenerative medicine. Accordingly, in this review paper, we summarized current knowledge related to the signaling pathways that are involved in the pericytes’ activation, pericytes-to-MSC transition, differentiation of tissue-resident stem cells, and MSC-dependent modulation of immune cell-driven inflammation, which are crucially responsible for regeneration of injured tissues.